A 67-Year-Old Male with Diffuse Purpuric Vesicles and Bullae - Zizi Yu; Yun Xue; Ruth Foreman; Daniela Kroshinsky (MDPI AG, 2020)
Leukocytoclastic vasculitis (LCV) is a small-vessel vasculitis that most commonly affects the postcapillary venules in the skin. It classically presents with purpuric macules that progress to palpable purpura on the bilateral shins 7-10 days after an inciting medication or infection, or in the setting of connective tissue disease, malignancy, or inflammatory bowel disease. Up to 50% of cases have no identifiable cause. Lesions on the buttocks, abdomen, upper extremities, and face are uncommon, as are bullae and ulcers. We present a rare case of bullous LCV manifesting as grouped vesicles on the face and body mimicking varicella-zoster infection.